2017
DOI: 10.19044/esj.2017.v13n13p426
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Support for Entrepreneurship Development on Economic Growth and Development in Nigeria

Abstract: This paper examines the effect of support for entrepreneurship development on economic growth and development in Nigeria with a view to ameliorating some problems militating against the development of Nigeria. Secondary data was sourced from CBN reports, NBS reports and so on. Hypotheses were set and tested by engaging the linear regression method as the analytical tool. The results discovered that government policy has helped in developing entrepreneurs' skill in Nigeria and that whatever polices formulated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Concept of Entrepreneurship Development Programmes Adelekan and Tijani (2017) observed that entrepreneurship development is the ability to envision and chart a course for a new business venture by combining information from the functional disciplines and from the external environment in the context of the extraordinary uncertainty and ambiguity which faces a new business venture. A greater percentage of jobs are created by entrepreneurs who started with small businesses (Mathew & Victor, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Concept of Entrepreneurship Development Programmes Adelekan and Tijani (2017) observed that entrepreneurship development is the ability to envision and chart a course for a new business venture by combining information from the functional disciplines and from the external environment in the context of the extraordinary uncertainty and ambiguity which faces a new business venture. A greater percentage of jobs are created by entrepreneurs who started with small businesses (Mathew & Victor, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…No doubt that the domain of entrepreneurship had witnessed an influx of research endeavours. Some of which studied Universities supporting students’ entrepreneurship tendency ( Adelekan and Tijani, 2017 ; Ahmed et al, 2020 ; Leung et al, 2020 ), entrepreneurial alertness for opportunity identification ( Kevin, 2016 ), career adaptability in predicting entrepreneurial intention including those with special needs ( Laramie et al, 2014 ; Leung et al, 2020 ). Related work in this domain was done by Michael and Doris (2001) , who examined personal initiative (PI) as an active performance concept for work in the 21st century.…”
Section: The Present Studymentioning
confidence: 99%
“…With the aforementioned, entrepreneurs who are potential trend setters are forced to fall back to their personal savings and loans from family and friends. Adelekan and Tijani (2017) emphasised on the high cost of doing business which makes the amount received from the sources insignificant to start the business thereby terminating business ideas that were ready for startup.…”
Section: Relevance Of Working Capital (Financial Empowerment) To Empl...mentioning
confidence: 99%
“…Education is a sustainable development that enables individuals to acquire knowledge, values and skills needed to make decisions as to how things can be done collectively either from the local or global perspective with the aim to improve the quality of life now and in the future. Entrepreneurs reasonably contribute to social and economic states of the nation via development of strategies and capabilities needed for proper coordination of resources, innovation and freedom of creativity (Adelekan and Tijani, 2017;as cited in Shariff and Saud, 2009). Entrepreneurial training serves as a way to develop the mind that bores creativity and equip such minds with meaningful skills that will sustain and increase creativity (Sitoula, 2015;as cited in Singer et al, 2012).…”
Section: Employment Creation and Sustainability Through Entrepreneuri...mentioning
confidence: 99%